Kidney transplantation across HLA and ABO antibody barriers - Becker, Luis Eduardo; Süsal, Caner; Morath, Christian (Current opinion in organ transplantation, 2013)
PURPOSE OF REVIEW: A significant number of kidney transplantations in industrialized countries is currently performed over human leukocyte antigen (HLA) or ABO antibody barriers after living donation to encounter the increasing shortage of organs from deceased donors. Although patients with moderate titers of anti-A/B antibodies may easily be desensitized with no negative impact on allograft survival, recipients with high titers and HLA sensitized patients demonstrate a substantial risk for antibody-mediated rejection, limiting long-term outcomes. - RECENT FINDINGS: The use of powerful desensitization strategies including plasmapheresis and immunoadsorption, extended therapeutic options such as the application of the recently introduced complement inhibitors, and refined antibody detection techniques may further facilitate transplantations, especially in the HLA-sensitized kidney transplant recipient. On the contrary, special strategies such as the Eurotransplant Acceptable Mismatch Program or kidney paired exchange help improving long-term outcomes in these difficult to transplant patients by circumventing the HLA (or ABO) antibody barrier. - SUMMARY: As compared with waiting for a compatible deceased donor organ, HLA and ABO incompatible transplantations performed in experienced centers have become a reasonable alternative for end-stage kidney disease patients with an incompatible live donor. Whenever possible, however, the transplantation should be performed between ABO compatible donor-recipient pairs in the absence of positive crossmatch results.
Gesehen am 03.12.2020
DOI funktioniert nicht